IMPLEMENTASI PELAKSANAAN PEMBELAJARAN SENI BUDAYA DI KELAS V SD 2 HONGGOSOCO - Siti Khoirotun Nisa; Darmawan Baihaqi; Wasis Wijayanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to deeply examine the history of the SD 2 Honggosoco educational institution, describe the process of implementing arts and culture learning, and analyze the supporting and hindering factors in the implementation of arts and culture learning. This research uses a qualitative method with a narrative approach. The research subjects are the fifth-grade teachers of SD 2 Honggosoco. Data collection techniques were carried out thru observation, interviews, and documentation. Data analysis used an interactive model that included data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of Arts and Culture learning in class V at SD 2 Honggosoco has been carried out according to the planning, implementation, and assessment stages based on the Merdeka Curriculum, with the application of project-based learning that actively involves students in art practice activities. Factors supporting the implementation of Arts and Culture learning include student enthusiasm, teacher creativity in using teaching methods and media, and school support in providing simple tools and materials. As for the inhibiting factors found, they are the limited learning time, inadequate art practice facilities and materials, and the lack of teacher training regarding the implementation of the art and culture learning model. This research is expected to serve as a basis for evaluation and reference in improving the quality of Arts and Culture learning implementation in elementary schools.